Extracorporeal Circulation Causes Release of Neutrophil Gelatinase-Associated Lipocalin (NGAL) - Per Jönsson; Marie-Louise Ståhl; Kjell Ohlsson (Mediators of Inflammation)
Extracorporeal circulation (ECC) used during cardiac surgery causes activation of several inflammatory systems. These events are not fully understood but are responsible for complications during the immediate postoperative period. Neutrophil gelatinase-associated lipocalin (NGAL), a member of the expanding lipocalin family, has recently been described as an inflammatory protein. In this study, the release of NGAL into the circulation in 41 patients undergoing heart surgery with ECC was evaluated. A 4- to 5-fold elevation of the concentration of NGAL in plasma was observed during the immediate postoperative course with a rapid elimination during the first postoperative day. Four patients undergoing lung surgery (without ECC) were also studied. The plasma concentration of NGAL only increased with a factor of 1.1-2.2 over the operation. We conclude that NGAL is released into the circulation during heart surgery, probably as a result of the inflammatory activation of leukocytes initiated by the extracorporeal circulation.